Trans-European networks: The white paper and beyond - Colin Turner (Intereconomics, 1994)
The desire to enhance the gains from the internal market programme has led the European Union (EU) to emphasize the importance of the development of a coherent set of infrastructure networks in the telecommunication, transport and energy sectors. What steps must be taken to realise such trans-European networks? How can the massive financing problems be overcome?
Keywords: 330